Risk Profiles for Barrett’s Esophagus Differ between New and Prevalent, and Long- and Short-Segment Cases - Tan, Mimi C. (PLoS One, 2016)
BACKGROUND: Previous studies on Barrett’s esophagus (BE) risk factors have had differing case definitions and control groups. The purpose of this study was to examine differences in risk factors between newly diagnosed vs. prevalent BE, long- vs. short-segment BE, and endoscopy-only BE without specialized intestinal metaplasia (SIM). METHODS: We conducted a cross-sectional study among eligible patients scheduled for elective esophagogastroduodenoscopy (EGD) and patients eligible for screening colonoscopy, recruited from primary care clinics at a Veterans Affairs center. All participants completed a survey on demographics, gastroesophageal reflux disease (GERD) symptoms and medication use prior to undergoing study EGD. We compared BE cases separately to two control groups: 503 primary care controls and 1353 endoscopy controls. Associations between risk factors and differing BE case definitions were evaluated with multivariate logistic regression models. RESULTS: For comparisons with primary care controls, early onset frequent GERD symptoms were more strongly associated with risk of long-segment BE (OR 19.9; 95% CI 7.96–49.7) than short-segment BE (OR 8.54; 95% CI 3.85–18.9). Likewise, the inverse association with H. pylori infection was stronger for long-segment BE (OR, 0.45; 95% CI, 0.26–0.79) than short-segment BE (OR, 0.71; 95% CI, 0.48–1.05). GERD symptoms and H. pylori infection was also more strongly associated with prevalent BE than newly diagnosed BE. Few differences were observed between BE cases and endoscopy controls. Endoscopy-only BE was associated with GERD symptoms (OR 2.25, 95% CI 1.32–3.85) and PPI/H2RA use (OR 4.44; 95% CI 2.61–7.54) but to a smaller degree than BE with SIM. CONCLUSION: We found differences in the strength and profiles of risk factors for BE. The findings support that epidemiological studies of BE should make a distinction between long and short, new and prevalent, endoscopy-only and BE with SIM as well as type of controls.